2019
DOI: 10.1080/15230430.2019.1565854
|View full text |Cite
|
Sign up to set email alerts
|

Young gravel-pit lakes along Canada’s Dempster Highway: How do they compare with natural lakes?

Abstract: Gravel-pit lakes are a common feature of many human-modified landscapes throughout the world. In Canada's north, they are often formed when gravel is extracted to construct dams, bridges, and highways. Past studies suggest that gravel-pit lakes differ from natural lakes in terms of their morphometry, water quality, and biological communities. In this study, we compared gravel-pit and natural lakes by sampling lakes between Inuvik and Fort McPherson in the Northwest Territories. We collected lake morphometry, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Consequently, the contact of the water to natural bedrock that is mainly composed of gneiss (Moores and Fairbridge, 2006) was reduced or prevented. In a study on young gravel pits in Canada, which, although located at lower elevations, are comparable to the mountain reservoirs in structure and age, however, significantly lower concentrations of phosphorus and nitrogen were found (Vucic et al, 2019). Another factor influencing the abiotic conditions in the mountain reservoirs was the origin of the water, though this aspect was not directly addressed here.…”
Section: Discussionmentioning
confidence: 90%
“…Consequently, the contact of the water to natural bedrock that is mainly composed of gneiss (Moores and Fairbridge, 2006) was reduced or prevented. In a study on young gravel pits in Canada, which, although located at lower elevations, are comparable to the mountain reservoirs in structure and age, however, significantly lower concentrations of phosphorus and nitrogen were found (Vucic et al, 2019). Another factor influencing the abiotic conditions in the mountain reservoirs was the origin of the water, though this aspect was not directly addressed here.…”
Section: Discussionmentioning
confidence: 90%
“…Our results indicated that GPPs have an important ecological role for floodplain wetland fishes and can compensate for wetland loss. Although our study focused only on floodplain wetland fishes, various types of organisms inhabit GPPs (including gravel pit lakes) (Emmrich et al, 2014; Santoul et al, 2009; Seelen et al, 2021; Søndergaard et al, 2018; Vucic et al, 2019; Zhao et al, 2016). Since ecological values often differ among taxa (e.g., Yamanaka et al, 2020), it is important to clarify the ecological value of GPPs for other floodplain wetland taxa in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Given the increased demand for geomaterials, the construction of GPPs may continuously increase in the future. Diverse organisms, such as fish, birds, plants, zooplankton, and macroinvertebrates, inhabit GPPs (including gravel pit lakes) (Emmrich et al, 2014; Santoul et al, 2009; Seelen et al, 2021; Søndergaard et al, 2018; Vucic et al, 2019; Zhao et al, 2016). Previous studies on human‐altered floodplain landscapes have examined the difference in macrophyte community structures between GPPs and other pooled water bodies, including artificial canals and natural lakes.…”
Section: Introductionmentioning
confidence: 99%
“…This culminated in relatively large nitrate levels, as the Harabhanga, Searsole and Dalurbandh Pit Lakes specifically receive domestic sewage through drainage systems from the nearby household. (Vucic et al 2019). However, it is possible that this is the pioneer work about the rotifer composition of the coal mine generated pit lake ecosystem in RCF.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably few biotic investigations were executed in these water bodies (Ferrari et al 2015) since these researches are complicated to perform and needs specialized methodologies (Woelfl and Whitton 2000). Researchers have, therefore, started to find out different ecological components in these ecosystems, biotic succession and population dynamics (Geller et al 2013;Wołowski et al 2013;Sienkiewicz and Gasiorowski 2015;Vucic et al 2019). The available information is inadequate to identify the trophic position of planktonic species in the mine lakes food system, which is different from that of more traditional lakes.…”
Section: Introductionmentioning
confidence: 99%